2018
DOI: 10.5539/ijsp.v7n3p22
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Excess Zeros in Count Data with Application to Antenatal Care Utilisation

Abstract: Poisson and negative binomial regression models have been used as a standard for modelling count outcomes; but these methods do not take into account the problems associated with excess zeros. However, zero-inflated and hurdle models have been proposed to model count data with excess zeros. The study therefore compared the performance of Zero-inflated (Zero-inflated Poisson (ZIP) and Zero-inflated negative binomial (ZINB)), and hurdle (Hurdle Poisson (HP) and Hurdle negative binomial (HNB)) models in determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…While these zeros are important and meaningful, most researchers often treat them as missing values or delete them. In other cases, the data is either transformed into a linear model (which violates the normality assumption) or coded as a categorical dummy variable where all zeros are considered as 'absent' and those observed as 'present' (Lewsey and Thomson, 2004;Yusuf et al 2018). Under such circumstances, the analysis becomes less useful and less informative if the interest is to determine the number of occurrences (Yusuf et al, 2018).…”
Section: Zero-inflated Poisson and Negative Binomial Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these zeros are important and meaningful, most researchers often treat them as missing values or delete them. In other cases, the data is either transformed into a linear model (which violates the normality assumption) or coded as a categorical dummy variable where all zeros are considered as 'absent' and those observed as 'present' (Lewsey and Thomson, 2004;Yusuf et al 2018). Under such circumstances, the analysis becomes less useful and less informative if the interest is to determine the number of occurrences (Yusuf et al, 2018).…”
Section: Zero-inflated Poisson and Negative Binomial Modelsmentioning
confidence: 99%
“…Zero-inflated model can distinguish between the two processes causing the excess zeros (Diallo et al, 2019;Yusuf et al 2018). A common feature of zero-inflated model is its ability to 1 Numbers in brackets denotes size of farmers selected in each community simultaneously produce two outcomes in count data models by: i.)…”
Section: Zero-inflated Poisson and Negative Binomial Modelsmentioning
confidence: 99%
“…A comparison of the performance of modified Poisson regression models like ZIP and Zero-inflated negative binomial (ZINB), and Hurdle Poisson(HP) and Hurdle negative binomial (HNB) 13 models in determining the factors associated with the number of ANC visits taken, have been made in such studies. A study in Nigeria conducted by Yusuf et al 14 revealed that ZINB and HNB fitted the data better than the ZIP or HP. Sekata 15 analyzed the determinants of the barriers in number of antenatal care service visits among pregnant women in rural Ethiopia.…”
Section: Iintroductionmentioning
confidence: 95%
“…A marginalized zero-inflated Poisson (ZIP) 11 model, a modified Poisson regression model (that accommodates the excess zeros) has been used for analyzing ANC counts obtained from Bangladesh Demographic and Health Survey (BDHS)data 12 . This type of modified count data model has been used widely in the literature for handling zero-inflated ANC data 12,[14][15] . A comparison of the performance of modified Poisson regression models like ZIP and Zero-inflated negative binomial (ZINB), and Hurdle Poisson(HP) and Hurdle negative binomial (HNB) 13 models in determining the factors associated with the number of ANC visits taken, have been made in such studies.…”
Section: Iintroductionmentioning
confidence: 99%
“…Hence, zero-inflated regression models can be used, which include excess zeros in modelling to address the problem of overdispersion in the data set (Hu et al, 2011; Staub & Winkelmann, 2013). The zero-inflated models, that is, either the zero-inflated Poisson (ZIP) or zero-inflated negative binomial (ZINB) model, assume that data come from two different populations (Yusuf et al, 2018). In one part, the outcome is always zero counts, and in the second part, count data follow a standard Poisson process.…”
Section: Introductionmentioning
confidence: 99%